Behavioral Effect of Plant Volatiles Binding to Spodoptera littoralis Larval Odorant Receptors - de Fouchier, Arthur; Sun, Xiao; Caballero-Vidal, Gabriela; Travaillard, Solène; Jacquin-Joly, Emmanuelle; Montagné, Nicolas (Frontiers in Behavioral Neuroscience, 2018)
Phytophagous insects use volatile organic compounds emitted by plants to orient towards their hosts. In lepidopteran pests, crop damages are caused by larval stages – the caterpillars – that feed extensively on leaves or other plant tissues. However, larval host plant choice has been poorly studied, and it is generally admitted that caterpillars feed on the plant where the female laid the eggs. The mobility of caterpillars has been generally overlooked even though several studies showed that they can orient towards odors and change host plant. Recently, a large number of odorant receptors (ORs) tuned to plant volatiles have been characterized in the model pest moth Spodoptera littoralis (Noctuidae). In the present work, we identified 9 of these deorphanized ORs as expressed in S. littoralis caterpillars. In order to understand whether these ORs are involved in host searching, we tested the behavioral significance of their ligands using a larval two-choice assay. This OR-guided approach led to the identification of 9 plant volatiles, namely 1-hexanol, benzyl alcohol, acetophenone, benzaldehyde, (Z)3-hexenol, (E)2-hexenol, indole, DMNT and (Z)3-hexenyl acetate, which are active on S. littoralis caterpillar behavior, increasing our knowledge on larval olfactory abilities. To further explore the link between OR activation and behavioral output induced by plant volatiles we used a modeling approach, thereby allowing identification of some ORs whose activation is related to caterpillar attraction. These ORs may be promising targets for future plant protection strategies.